NEW SAMPLES OF TRITICUM COMPACTUM HOST. FROM NAKHCHIVAN AUTONOMOUS REPUBLIC - Kh. R. Rustamov (Вавиловский журнал генетики и селекции)
This article analyzes new data on compactum wheat (Triticum compactum Host.) collected in the Nakhchivan Autonomous Republic (NAR). Two expeditions to various parts of AR, supported by the Science Development Foundation, along with other species, collected 78 accessions of compactum wheat belonging to the groups of varieties convar. rigidicompactum, convar. inflatum, and convar. compactum. The majority of samples (85,5 %) belonged to the varieties var. splendidorigidum, var. fetissovii, var. asiaticicterinum, var. erinaceum, etc., which are a subgroup of subconvar. rigidicompactum. A wide intraspecific variability in growth habit, earing data, resistance to yellow rust, height, architectonic of plants, and ear parameters was revealed.